Prevalence of Erectile Dysfunction among Turkish Heterosexual Men - Akpinar, E.; Uysal, Y.; Bozdemir, N.; Saatci, E.; Bashan, I. (Scientific Journal of Medical Science, 2013)
Erectile dysfunction (ED) is defined as the inability to attain or maintain an erection sufficient for satisfactory sexual performance and is one of the main complaints in male sexual medicine. We conducted an internet survey to determine the frequency and severity of ED in a group of Turkish men. The online survey was randomly offered to web surfers in Turkey. The survey was posted on the Internet with the title ‘‘Sexual Health Survey for Men”. The web address (www.cu.edu.tr/family) was hosted by the Cukurova University. Cukurova University Department of Family Medicine provided a link on the online site. Only one survey per computer could be completed (unique IP recognition). Surveys could not be returned to later nor could earlier entries be revised. The survey was designed to collect basic medical, sociodemographic characteristics and comorbidities as they may relate to erectile dysfunction include the Sexual Health Inventory for Men (SHIM). The data were installed and analyzed using the Statistical Package for Social Sciences software, version 15.0 (SPSS Inc., Chicago, IL, USA). Chi-square, Mann-Whitney, Kruskal-Wallis and Pearson's correlation coefficient tests were used for statistical analysis. A total of 1809 [137(7.57%) were excluded due to inclusion criteria] participants were enrolled. The mean score of erectile dysfunction was 17.87±4.56 (range 1–25, 95% confidence interval [CI] 1.34). The mean age of subjects was 38.6±10.3 years (range 18–79). The overall prevalence of erectile dysfunction of various degrees was 79.2%. There was a significant relationship between different degrees of erectile dysfunction and age; it was significantly higher in patients older than 50 years of age (p=0.001). Erectile dysfunction was more common in patients with BMI >25 (p = 0.001). Sexuality is a sensitive issue that may be difficult to explore through surveys involving direct contact. Online surveys may provide more anonymity and less direct contact encouraging participation. Our study suggests that erectile dysfunction is a major health concern of Turkish males.